Bladder cancer precision-cut tumor slices (PCTS) preserve functional immune microenvironment enabling ex vivo drug evaluation - Sarah Richtmann; Maja Radak; Viktor Sincic; Jenny Hugoson; Nadja Werner; Valeriia Skoryk; Darcy Wagner; Fredrik Liedberg; Kristina Lundberg (BMC Medicine, 2026)
Abstract Background The development of effective cancer immunotherapies is hindered by the lack of preclinical models that faithfully preserve tumor-immune interactions. Current approaches provide limited representation of immune components, creating a critical translational gap between laboratory findings and clinical outcomes. Precision Cut Tumor Slices (PCTS) offer a promising solution by maintaining complete tumor architecture including native immune cell populations and spatial organization. Methods We established a PCTS platform using fresh bladder cancer specimens and optimized culture conditions to preserve tissue integrity and cell viability. Comprehensive phenotyping was performed using flow cytometry to characterize tumor and immune cell populations. Immune functionality was validated through CD3/CD28 stimulation experiments measuring activation markers (CD69, CD137, HLA-DR) and cytokine secretion. Nine patient samples were treated with the PD-1 checkpoint inhibitor nivolumab to assess ex vivo effects. Additionally, multiplex immunofluorescence microscopy was employed on fixed PCTS as a readout for spatial distribution and cytotoxic effects of chemotherapy agents. Results PCTS maintained viability of both cancer cells and diverse immune populations for up to six days. Functional validation demonstrated immune responsiveness upon T cell stimulation, with elevated activation markers and significantly increased secretion of inflammatory mediators including IFNγ and CXCL10, in treated as compared to control samples. The platform successfully addressed intra-tumor heterogeneity while maintaining experimental reproducibility across patient samples. Treatment with nivolumab revealed heterogeneous responses, with two out of nine samples (22%) demonstrating dose-dependent immune activation in the PCTS model, consistent with published response rates. Multiplex immunofluorescence analysis confirmed the ability to capture both immune-mediated responses and direct cytotoxic effects on cancer cells, enabling comprehensive evaluation of combination therapies. Conclusions This validated PCTS platform represents a versatile human-derived tool for evaluating cancer immunotherapies while maintaining physiological tumor microenvironment complexity. The technical foundation established here enables future prospective studies correlating ex vivo responses with patient clinical outcomes, potentially advancing personalized treatment selection and reducing reliance on animal models in immunotherapy development.